Active aging in Latin America: Narrative review of the literature - Favela Ocaño, María Alejandra; Castro Vásquez, María del Carmen (Horizonte Sanitario, 2024)
Objective: To present a narrative review of the literature on active aging in Latin America. Material and methods: The search for articles was carried out in the EBSCO Host, Web of Science, SciELO, Redalyc, Dialnet plus, JSTOR, Google Scholar and CLACSO Library databases, considering those that included people aged 60 and over, carried out in any country in Latin America, in Spanish, English and Portuguese, published from 2011 to 2021, open access to the full text. The descriptors used were: aging, active aging/active aging, healthy aging/healthy aging/Envelhecimento Saudável, successful aging/successful aging/envelhecimento bem sucedido, older people/elderly/Idosos, Latin America/América Latina/Latin America. The boolean operator was "AND". Results: 36 articles were obtained, which were organized into four points: 1) active aging and its approach, 2) scales to measure active aging, 3) meanings and perception of active aging, 4) strategies to promote active aging and the major obstacles to putting it into practice. There is an incipient scientific production in Latin America compared to the European continent. The country with the most published articles is Brazil, followed by Mexico and Colombia, where the active aging approach formulated by the WHO is most frequently used. Most of them were published in 2020. Conclusions: There is an incipient scientific production compared to the European continent. The main contribution of the review is to make active aging visible, showing areas of opportunity such as using mixed methods, the development of measuring instruments, the need for multidisciplinary work, and carrying out longitudinal studies accompanied by the perspective of the course of life. It is also necessary to work on the construction of active aging from childhood, as well as how to prevent ageism. The limitations are related to the complexity of the relationship between the pillars and the determinants, which can hinder practice and research.